A Sociolinguistic Analysis on Register Used By Student Regiment In Muhammadiyah University of Surakarta - Listianingrum, Sri Meilani (2012)
This research aims to describe the linguistics forms, the meanings and the function of register used by Student Regiment in Muhammadiyah University of Surakarta The research is descriptive qualitative. The data are in the form words and compound words. To collect data, the writer uses observation and documentation method. The data are analyzed based on the linguistic forms, meanings, and functions. In analyzing them, the writer employs the theory proposed by Halliday and Biber Douglas. The results of the study show that: 1) The linguistic forms of the register are divided into two, they are: words and compound wors. Register in the form of word consists of three categories; noun, verb, and adjective. While the register in the form of compound word also consists of three categories; noun, verb, and adjective. 2) The meanings of register are divided into three categories, they are; (a) based on the field the registers are used, there are 6 meanings: when they are in a training, when they are informing the recent condition, when they are giving such kind of command, when they are taking care of something, when they write an announcement, when they have a conversation in daily activity. (b) based on the mode, the register of Student Regiment is in the form of written and spoken. (c) based on the tenor, the register is used by two types, first, between commandant (the highest level position) to his members, second, the member in the same level such as staff to staff or member to member. 3) Based on the data, every register has its own function according the context of the situation.